Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the system of equations, we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy all three of the equations simultaneously. The system given is:
1. [tex]\( y = 2x^2 + 3 \)[/tex]
2. [tex]\( 5x^2 - 2y = x \)[/tex]
3. [tex]\( 3y - 4x = 51 \)[/tex]
Let's solve this step-by-step.
### Step 1: Substitute [tex]\( y \)[/tex] from Equation 1 into Equations 2 and 3
Substitute [tex]\( y = 2x^2 + 3 \)[/tex] into the second equation [tex]\( 5x^2 - 2y = x \)[/tex]:
[tex]\[ 5x^2 - 2(2x^2 + 3) = x \][/tex]
[tex]\[ 5x^2 - 4x^2 - 6 = x \][/tex]
[tex]\[ x^2 - x - 6 = 0 \][/tex]
This is a quadratic equation. Let's solve for [tex]\( x \)[/tex] using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -6 \)[/tex]:
[tex]\[ x = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-6)}}{2(1)} \][/tex]
[tex]\[ x = \frac{1 \pm \sqrt{1 + 24}}{2} \][/tex]
[tex]\[ x = \frac{1 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{1 \pm 5}{2} \][/tex]
So, the solutions for [tex]\( x \)[/tex] are:
[tex]\[ x = \frac{1 + 5}{2} = 3 \][/tex]
[tex]\[ x = \frac{1 - 5}{2} = -2 \][/tex]
### Step 2: Find Corresponding [tex]\( y \)[/tex] Values
For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 2(3)^2 + 3 \][/tex]
[tex]\[ y = 2 \times 9 + 3 \][/tex]
[tex]\[ y = 18 + 3 \][/tex]
[tex]\[ y = 21 \][/tex]
For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = 2(-2)^2 + 3 \][/tex]
[tex]\[ y = 2 \times 4 + 3 \][/tex]
[tex]\[ y = 8 + 3 \][/tex]
[tex]\[ y = 11 \][/tex]
### Step 3: Verify in the Third Equation
Check if both pairs [tex]\((x, y) = (3, 21)\)[/tex] and [tex]\((-2, 11)\)[/tex] satisfy the third equation [tex]\( 3y - 4x = 51 \)[/tex]:
For [tex]\( (3, 21) \)[/tex]:
[tex]\[ 3(21) - 4(3) = 51 \][/tex]
[tex]\[ 63 - 12 = 51 \][/tex]
[tex]\[ 51 = 51 \][/tex]
This pair is a solution.
For [tex]\( (-2, 11) \)[/tex]:
[tex]\[ 3(11) - 4(-2) = 51 \][/tex]
[tex]\[ 33 + 8 = 41 \][/tex]
[tex]\[ 41 \neq 51 \][/tex]
This pair is not a solution.
### Conclusion
The solution to the system of equations is:
[tex]\[ x = 3 \][/tex]
[tex]\[ y = 21 \][/tex]
Therefore, the only solution to the system is [tex]\((3, 21)\)[/tex].
1. [tex]\( y = 2x^2 + 3 \)[/tex]
2. [tex]\( 5x^2 - 2y = x \)[/tex]
3. [tex]\( 3y - 4x = 51 \)[/tex]
Let's solve this step-by-step.
### Step 1: Substitute [tex]\( y \)[/tex] from Equation 1 into Equations 2 and 3
Substitute [tex]\( y = 2x^2 + 3 \)[/tex] into the second equation [tex]\( 5x^2 - 2y = x \)[/tex]:
[tex]\[ 5x^2 - 2(2x^2 + 3) = x \][/tex]
[tex]\[ 5x^2 - 4x^2 - 6 = x \][/tex]
[tex]\[ x^2 - x - 6 = 0 \][/tex]
This is a quadratic equation. Let's solve for [tex]\( x \)[/tex] using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -6 \)[/tex]:
[tex]\[ x = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-6)}}{2(1)} \][/tex]
[tex]\[ x = \frac{1 \pm \sqrt{1 + 24}}{2} \][/tex]
[tex]\[ x = \frac{1 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{1 \pm 5}{2} \][/tex]
So, the solutions for [tex]\( x \)[/tex] are:
[tex]\[ x = \frac{1 + 5}{2} = 3 \][/tex]
[tex]\[ x = \frac{1 - 5}{2} = -2 \][/tex]
### Step 2: Find Corresponding [tex]\( y \)[/tex] Values
For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 2(3)^2 + 3 \][/tex]
[tex]\[ y = 2 \times 9 + 3 \][/tex]
[tex]\[ y = 18 + 3 \][/tex]
[tex]\[ y = 21 \][/tex]
For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = 2(-2)^2 + 3 \][/tex]
[tex]\[ y = 2 \times 4 + 3 \][/tex]
[tex]\[ y = 8 + 3 \][/tex]
[tex]\[ y = 11 \][/tex]
### Step 3: Verify in the Third Equation
Check if both pairs [tex]\((x, y) = (3, 21)\)[/tex] and [tex]\((-2, 11)\)[/tex] satisfy the third equation [tex]\( 3y - 4x = 51 \)[/tex]:
For [tex]\( (3, 21) \)[/tex]:
[tex]\[ 3(21) - 4(3) = 51 \][/tex]
[tex]\[ 63 - 12 = 51 \][/tex]
[tex]\[ 51 = 51 \][/tex]
This pair is a solution.
For [tex]\( (-2, 11) \)[/tex]:
[tex]\[ 3(11) - 4(-2) = 51 \][/tex]
[tex]\[ 33 + 8 = 41 \][/tex]
[tex]\[ 41 \neq 51 \][/tex]
This pair is not a solution.
### Conclusion
The solution to the system of equations is:
[tex]\[ x = 3 \][/tex]
[tex]\[ y = 21 \][/tex]
Therefore, the only solution to the system is [tex]\((3, 21)\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.